PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA DAN KOMITMEN ORGANISASIOANAL ( STUDI PADA SEKRETARIAT DAERAH KABUPATEN PATI ) - 11.42.02.0114, Slamet (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this research is to examine and analyze the effect of motivation on employee performance mediated by job satisfaction and organizational commitment . In this study, the population was an civil government employee at the District Secretariat of Pati Regency , amounting to 215 peoples. In this research, sampling using purposive sampling. The criteria used in the determination of this sample is Pati District Secretariat officials who have a service life over 10 years and a minimum of high school education. So, the number of samples in this study were 123 respondents. Testing methods using regression and path analysis with test results as follows: (1) motivation positive and significant effect on job satisfaction, (2) motivation positive and significant impact on organizational commitment, (3) job satisfaction positive influential and significant to organizational commitment, (4) motivation positive and significant impact on the performance of employees, (5) job satisfaction and a significant positive effect on employee performance, (6) organizational commitment and significant positive effect on employee performance, (7) job satisfaction proved to mediate the influence of motivation on employee performance , (8) organizational commitment shown to mediate pengarhun motivation on employee performance, (9) job satisfaction and organizational commitment shown to mediate the effect of motivation on employee performance Keywords : motivation, job satisfaction, organizational commitment and employee performance.